Conservation of Soil Physical and Chemical Properties by Application of Compost and Biochar in Tambakrejo Village, Malang Regency - Wibowo, Febri Arif Cahyo; Alkornea, Dea; Chanan, Mochamad (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Soil degradation is often indicated by reduced land productivity, which affects soil physical, chemical, and biological properties. The application of compost and biochar fertilizer serves as an alternative method for improving the physical and chemical properties of the soil. This study was conducted to determine the effect of applying compost and biochar to the soil on its physical and chemical properties. The research was conducted in Tambakrejo Village, Sumbermanjing Wetan, South Malang. The study employed a Randomized Complete Block Design (RCBD) with four treatments: control (P0), 15 kg of compost and 5 kg of biochar (P1B3), 10 kg of compost and 10 kg of biochar (P2B2), and 5 kg of compost and 15 kg of biochar (P3B1). The results indicated that the most effective application of compost and biochar in improving bulk density, soil temperature, Corganic, and available P content of the soil was the P3B1 treatment. The composition of compost and biochar P2B2 was found to increase soil pH. Additionally, the composition of P1B3 increased soil moisture, total N, and total K. Based on the results, the application of compost and biochar can reduce soil bulk density, improve soil temperature, pH, and moisture, as well as increase soil Corganic and NPK content.